Energetics for interfaces between group IV transition metal carbides and bcc iron - Jung, Woo-Sang; Lee, Seung-Cheol; Chung, Soon-Hyo (IRON STEEL INST JAPAN KEIDANREN KAIKAN, 2008)
An ab initio study was carried out on interfacial energies and misfit strain energies at coherent interfaces between Fe(bcc structure) and MCs(NaCl structure, M=Ti, Zr, Hf). The interfacial energies at relaxed interfaces, Fe/TiC, Fe/ZrC and Fe/HfC, were 0.263, 0.153 and 0.271 J/m(2), respectively. The influence of bond energy was estimated using the discrete lattice plane/nearest neighbor broken bond model. It was found that the dependence of interfacial energy on the type of carbide was closely related to changes of the bond energies between Fe, M and C atoms before and after formation of the interfaces Fe/MC. The misfit strain energies in Fe/TiC, Fe/ZrC and Fe/HfC systems were 0.390, 1.692 and 1.408 eV per 16 atoms (Fe; 8 atoms and MC; 8 atoms). The misfit strain energy became larger when the difference in lattice parameters between the bulk Fe and the bulk MCs increased.